IN VITRO-IN VIVO EVALUATION OF FAST-DISSOLVING TABLETS CONTAINING SOLID DISPERSION OF OXCARBAZEPINE - Mohan, Arti; Sangeetha, G. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Investigation of in vitro/in vivo behaviour of fast-dissolving tablets containing solid dispersions of oxcarbazepine is the focus of the present research work. Methods: The effect of various hydrophilic polymers on the aqueous solubility of oxcarbazepine was studied. Polyethylene glycol 6000 carrier was selected and solid dispersions were prepared by various methods. A total of nine formulations were compressed into fast-dissolving tablets using avicel PH 102 as a directly compressible filler and ac-di-sol, sodium starch glycolate and crospovidone as super disintegrants and evaluated for pre and post compression parameters and in vitro drug release. In vivo studies of the pure drug, optimized formulation and marketed formulation were carried out on male Wistar rats and pharmacokinetic parameters were calculated using the pk function for Microsoft excel. Results: Mathematical analysis of in vitro data suggested that the first order was the most suitable mathematical model for describing the optimized formulation. The first-order plot was found to be fairly linear for optimized formulation as indicated by its high regression value. Stability studies indicated that the effect of storage was insignificant at 5% level of confidence. The optimized formulation has shown Tmax of 0.5 h, which was highly significant (P<0.05) when compared with pure drug and marketed formulation. Conclusion: Therefore, the solid dispersions prepared by melting method using polyethylene glycol 6000 as hydrophilic carrier can be successfully used for the improvement of dissolution of oxcarbazepine and resulted in faster onset of action as indicated by in vitro and in vivo studies.